2006
DOI: 10.1038/nn1639
|View full text |Cite
|
Sign up to set email alerts
|

Variable channel expression in identified single and electrically coupled neurons in different animals

Abstract: It is often assumed that all neurons of the same cell type have identical intrinsic properties, both within an animal and between animals. We exploited the large size and small number of unambiguously identifiable neurons in the crab stomatogastric ganglion to test this assumption at the level of channel mRNA expression and membrane currents (measured in voltage-clamp experiments). In lateral pyloric (LP) neurons, we saw strong correlations between measured current and the abundance of Shal and BK-KCa mRNAs (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

43
488
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 426 publications
(532 citation statements)
references
References 41 publications
43
488
0
1
Order By: Relevance
“…Therefore, altered neuronal network states in BD arise from different sets of risk variants in different individuals, showing that in BD these unstable physiological network fates can be reached by many distinct molecular mechanisms (31). Theoretical and experimental studies in animal models have demonstrated that identical activity in neuronal circuits can arise from many different patterns of ion channel gene expression (32,33). Similarly, we hypothesize that cellular differences in neuronal excitability underlying susceptibility to mania and depression can arise from distinct combinations of ion channel variants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, altered neuronal network states in BD arise from different sets of risk variants in different individuals, showing that in BD these unstable physiological network fates can be reached by many distinct molecular mechanisms (31). Theoretical and experimental studies in animal models have demonstrated that identical activity in neuronal circuits can arise from many different patterns of ion channel gene expression (32,33). Similarly, we hypothesize that cellular differences in neuronal excitability underlying susceptibility to mania and depression can arise from distinct combinations of ion channel variants.…”
Section: Discussionmentioning
confidence: 99%
“…Ionic channel gating and vesicle release vary stochastically (Sakmann and Neher 2009;Yang and Xu-Friedman 2013), channel number and synaptic strengths vary (Roffman et al 2012;Schulz et al 2006), neuron properties may vary (Benjamin 1976), motor neuronal output varies (Williams et al 2013), neuromodulation alters responses (Marder 2012), body mechanics alters responses to neural output (Chiel et al 2009), and environmental loads may vary unexpectedly (Johansson and Westling 1988).…”
mentioning
confidence: 99%
“…Some neuronal networks, for example, can produce rhythmic outputs that are remarkably stable in the face of clear differences in the detailed makeup of the neurons that compose them (Schulz et al 2006, Marder 2011. At the same time, external inputs can change the functioning of both individual neurons and the networks as a whole (Nusbaum and Blitz 2012).…”
Section: Challenge 1: Understanding Living Organisms As Multiscale Symentioning
confidence: 99%